2023
DOI: 10.3390/horticulturae9070847
|View full text |Cite
|
Sign up to set email alerts
|

Asexual Propagation of Greek Salvia officinalis L. Populations Selected for Ornamental Use

Abstract: Salvia officinalis, commonly known as sage, is highly valued for its medicinal and ornamental properties. In the present work, 12 native sage populations of north-west Greece were evaluated for eight ornamental traits. Populations from the locations of Aristi, Kefalovryso and Igoumenitsa were selected as the best performing and for their preservation and availability in the market, their asexual propagation was investigated by (a) shoot cutting and (b) in vitro techniques. Propagation by cuttings was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The previous literature reported that Salvia species suffer from seed dormancy [34,35]. Furthermore, most of the previous studies documented the use of axillary buds to initiate the in vitro culture [36][37][38].…”
Section: Plant Sterilization and In Vitro Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous literature reported that Salvia species suffer from seed dormancy [34,35]. Furthermore, most of the previous studies documented the use of axillary buds to initiate the in vitro culture [36][37][38].…”
Section: Plant Sterilization and In Vitro Establishmentmentioning
confidence: 99%
“…The axillary buds are an asexual propagation method that gives genetically identical plants to the mother plants rather than seeds [36,38]. According to our objective, we tried to produce a sustainable protocol to conserve this valuable plant and apply this protocol in the future in order to return this valuable plant to its environment after the acclimatization process, with fewer variations in the produced plants.…”
Section: Plant Sterilization and In Vitro Establishmentmentioning
confidence: 99%